Methane's Solar Radiative Forcing - R. E. Byrom; K. P. Shine (Geophysical Research Letters)
Abstract Methane (CH4) has significant absorption bands at wavelengths of 1.7, 2.3, 3.3 and 7.6 μm which absorb incoming solar ‘shortwave’ (SW) radiation and contribute to radiative forcing (RF). A comprehensive quantification of CH4 SW RF is presented using a narrow‐band radiative transfer model to calculate spatially and monthly resolved estimates of CH4 SW RF and its impact on longwave (LW) stratospheric temperature adjusted RF (SARF). These new calculations include satellite measurements of CH4 distribution and spectrally varying surface albedo, and include absorption of solar mid‐infrared radiation by methane's 7.6 μm band. These factors substantially influence methane's SW effect. For a 750–1,800 ppb perturbation, the all‐sky top‐of‐atmosphere SW instantaneous RF is 0.082 W m−2; at the tropopause it is 0.002 W m−2, considerably smaller than previous estimates. Including the impact of SW absorption on stratospheric temperature increases tropopause SARF by 0.039 W m−2 (or 7%) compared to the LW‐only SARF.